Evaluating the recovery potential of CH4 by injecting CO2 mixture into marine hydrate-bearing reservoirs with a new multi-gas hydrate simulator. (10th August 2022) - Tian, Hailong; Yu, Zimeng; Xu, Tianfu; Xiao, Ting; Shang, Songhua
Abstract: The conventional exploitation technologies (depressurization, thermal stimulation, and chemical inhibitor injection) of natural gas hydrate (NGH) are easy to induce environmental and geological problems. An alternative way of NGH exploitation using CO2 replacement method is the most promising technology, because it offers a dual purpose of CH4 safe recovery and CO2 sequestration in a form of hydrate. To evaluate the recovery potential of CH4 by injecting CO2 mixture into a marine hydrate-bearing reservoir, a simulator capable of modeling the behaviors of multi-gas hydrate-bearing geologic systems was newly developed. The simulator was applied to evaluate the recovery efficiency of CH4 by injecting CO2 mixture into a marine hydrate-bearing reservoir at SH2 site in the South China Sea. The simulated results suggest that by performing the similar operational procedures used in the Iġnik Sikumi #1 field trial, the recovery efficiency of CH4 by injecting CO2 mixture reaches about 6.95%, and the storage ratio of CO2 is about 0.3. The results of sensitivity analysis show that decreasing the concentration of CO2 in the mixtures can improve the recovery efficiency of CH4, but simultaneously reduce the storage ratio of CO2 . The higher initial saturation of free water reduces the recovery efficiency of CH4, while increases the storage ratio of CO2 . This work is significant to the safe exploitation of NGH and to the climate change mitigation through sequestering CO2 in the geological formation. Highlights: A simulator for modeling multi-gas hydrates in geologic systems was developed. Potentials of CO2 storage and CH4 recovery at SH2 site were evaluated. Higher CO2 in injectant increases CO2 storage ratio but decreases CH4 recovery efficiency. Higher initial water saturation reduces CH4 recovery efficiency but improves CO2 storage ratio.